Clinical rabies: is cure possible? - Mohan, Mithun C; K, Sudeep; ., Nived; K, Pramod V; Kumar, Ajith; S, Prasanna Kv; P V, Narayanan (International Journal of Research in Medical Sciences, 2017)
Rabies is a fatal disease in humans and till date survivors of the disease after the clinical onset of the illness are rare. The approach to management of rabies is usually palliative. In rare cases of paralytic rabies a trial for cure has been tried. No single therapeutic agent is likely to be effective, but a combination of specific therapies could be considered, including rabies vaccine, rabies immunoglobulin, monoclonal antibodies, ribavirin, interferon alpha, ketamine etc. the only reported cases in literature were with rare success of the Milwaukee protocol. This is the case report of a 45 year old male who presented with clinical rabies and was started on the trial. Has the treatment had any benefit is to be debated and further options discussed.